2020
DOI: 10.1063/4.0000033
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous two-color snapshot view on ultrafast charge and spin dynamics in a Fe-Cu-Ni tri-layer

Abstract: Ultrafast phenomena on a femtosecond timescale are commonly examined by pump-probe experiments. This implies multiple measurements, where the sample under investigation is pumped with a short light pulse and then probed with a second pulse at various time delays to follow its dynamics. Recently, the principle of streaking extreme ultraviolet (XUV) pulses in the temporal domain has enabled recording the dynamics of a system within a single pulse. However, separate pump-probe experiments at different absorption … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 43 publications
6
13
0
Order By: Relevance
“…In addition, Figure 3 shows that transient absorption changes for different applied fields do not systematically start at t = 0: the same dynamics are observed for both field directions during the first tens of fs after optical excitation for E = 64.6, 65.7, and 66.3 eV (highlighted grey regions). At first glance, this is in line with the recent observation of a delay between ultrafast electronic and magnetic dynamics [30,34]. For E = 65.7 eV, a closer look at the first 100 fs reveals a crossing between H + and H − curves.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…In addition, Figure 3 shows that transient absorption changes for different applied fields do not systematically start at t = 0: the same dynamics are observed for both field directions during the first tens of fs after optical excitation for E = 64.6, 65.7, and 66.3 eV (highlighted grey regions). At first glance, this is in line with the recent observation of a delay between ultrafast electronic and magnetic dynamics [30,34]. For E = 65.7 eV, a closer look at the first 100 fs reveals a crossing between H + and H − curves.…”
Section: Resultssupporting
confidence: 88%
“…Furthermore, their calculations suggested that, in addition to the pure absorption spectra, the MCD should also be affected on sub-picosecond timescales. While subsequent experiments remained limited to the L-edges of transition metals [17], very recent work by Yao et al [34] and Rösner et al [30] unveiled that similar effects can also be observed at the M-edges of Fe, Co, and Ni. Furthermore, both studies demonstrated that, depending on the probing energy, a delay between the magnetic and pure charge dynamics (up to 100 fs) can exist.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The benefit for XFEL science has already been proven in two user experiments. In an experiment at the DiProI beamline at FERMI, the two-spot scheme using a superimposed grating of duty cycle of d = 0.5 or shift of s = 0.5 was used in a time-streaking experiment with two incident energies [34]. The same approach enabled the first user experiment at the SCS beamline at the European XFEL.…”
Section: Discussionmentioning
confidence: 99%
“… 9 Several important experimental techniques had being developed within the FERMI laboratories, such as EUV transient-grating (TG) and EUV magnetic-TG, 10,11 simultaneous time, and two-color spectroscopy. 12,13 Motivated by the rapidly growing field of the so-called femtomagnetism, 14 we have designed, built, and commissioned a novel and effective polarimeter for ultrafast magneto-optical experiments in the EUV photon energy range.…”
Section: Introductionmentioning
confidence: 99%